Sons of the Buddha : Continuities and Ruptures in a Burmese Monastic Tradition. - Carbine, Jason A. (Religion and Society., 2011)
Intended as a contribution to the study of religion and society, this book examines Buddhist monasticism in Myanmar. The book focuses on the Shwegyin, one of the most important but least understood monastic groups in the country. It illuminates key aspects of monastic and wider Burmese Buddhist thought and practice, and ultimately argues for the distinctiveness of elements of that thought and practice in comparison to the Buddhist cultures of Sri Lanka and Laos.